Reynolds, G., "Was George Fox a Gnostic? An Examination of Foxian Theology from a Valentinian Gnostic Perspective" - Ambler, Rex (Quaker studies, 2007)
REYNOLDS, G., Was George Fox a Gnostic? An Examination of Foxian Theology from a Valentinian Gnostic Perspective (Lewiston, NY: Edwin Mellen Press, 2005), pp. iv + 277 ISBN 0-7734-5901-4, Cloth, £69.95.